Analyzing the impromptu speech style of a job-hunting reality TV show host: a case study of "It's You" - He, Jingfan; Gao, Biao; Razi, Aishah Hj Mohammad
In the post-epidemic era, the employment situation has become increasingly serious, and job-hunting reality shows have innovated significantly to meet the current market demand. Given the diverse nature of the live context involved in these programs, it is crucial for the hosts to possess strong improvisational speech skills. However, some hosts struggle to effectively handle the various scenarios presented in the program, leading to ineffective communication. Therefore, this study focuses on the TV show “It’s You” as the research corpus and employs discourse control acts theory, discourse analysis, and descriptive statistics to examine the patterns of impromptu speech initiation by the hosts of this job-seeking reality show. In this study, the job-hunting reality show is divided into three stages, with the second stage, known as the multiple interaction stage, chosen as the focus of the analysis. Within this stage, two situational contexts are identified and a total of seven initiation words and twelve initiation sentences are summarized. Furthermore, quantitative statistics are conducted by considering the initiation object and initiation position. Based on the findings, two distinct expression patterns are identified: the suit deepening + derivative penetration + intersectional embedding mode, and the continuity + insertion jump + homeopathic deepening mode.